In pursuit of our ancestors' hand laterality. Issue 111 (October 2017) - Bargalló, Amèlia; Mosquera, Marina; Lozano, Sergi
Abstract: The aim of this paper is to apply a previously published method (Bargalló and Mosquera, 2014) to the archaeological record, allowing us to identify the hand laterality of our ancestors and determine when and how this feature, which is exhibited most strongly in humans, appeared in our evolutionary history. The method focuses on identifying handedness by looking at the technical features of the flakes produced by a single knapper, and discovering how many flakes are required to ascertain their hand preference. This method can potentially be applied to the majority of archaeological sites, since flakes are the most abundant stone tools, and stone tools are the most widespread and widely-preserved remains from prehistory. For our study, we selected two Spanish sites: Gran Dolina-TD10.1 (Atapuerca) and Abric Romaní (Barcelona), which were occupied by pre-Neanderthal and Neanderthal populations, respectively. Our analyses indicate that a minimum number of eight flakes produced by the same knapper is required to ascertain their hand preference. Even though this figure is relatively low, it is quite difficult to obtain from many archaeological sites. In addition, there is no single technical feature that provides information about handedness, instead there is a combination of eight technical features, localised on the striking platforms and ventral surfaces. The raw material is not relevant where good quality rocks are used, in this case quartzite and flint, since most of them retain the technical features required for the analysis. Expertise is not an issue either, since the technical features analysed here only correlate with handedness (Bargalló and Mosquera, 2014). Our results allow us to tentatively identify one right-handed knapper among the pre-Neanderthals of level TD10.1 at Gran Dolina (Atapuerca), while four of the five Neanderthals analysed from Abric Romaní were right-handed. The hand preference of the fifth knapper from that location (AR5) remains unclear.